2009
DOI: 10.3766/jaaa.20.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Hearing Screening Speeds Diagnosis and Access to Intervention by 20–25 Months

Abstract: The age at achievement of benchmarks such as diagnosis, fitting of amplification, and enrollment in early intervention in children who were screened for hearing loss is on target with stated goals provided by the Academy of Pediatrics and the Joint Committee on Infant Hearing. In addition, children who are not screened for hearing loss continue to show dramatic delays in achievement of benchmarks by as much as 24 months. Evaluating achievement of benchmarks during the start-up period of NHS programs allowed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
1
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 14 publications
(24 reference statements)
2
55
1
5
Order By: Relevance
“…Além disso, afirmativas anteriores 18 alertam que ao se utilizar apenas do PEATE com estímulo click ou mesmo o click associado ao PEATE-FE em frequências baixas, há o risco de se diagnosticar como perda auditiva leve às perdas auditivas em rampa.…”
Section: Discussionunclassified
“…Além disso, afirmativas anteriores 18 alertam que ao se utilizar apenas do PEATE com estímulo click ou mesmo o click associado ao PEATE-FE em frequências baixas, há o risco de se diagnosticar como perda auditiva leve às perdas auditivas em rampa.…”
Section: Discussionunclassified
“…Among developing countries Oman is the first country to implement nationwide UNHS [5]. Before the implementation of UNHS, studies have documented lot of variability in the age of identification and intervention; however, AOI has plummeted substantially after the implementation of UNHS [6,7,8]. A number of studies have been undertaken in different countries to see if a particular pattern emerges in terms of ages of suspicion, identification and intervention [9,10,11].…”
Section: Introductionmentioning
confidence: 97%
“…The Wessex findings have been replicated in a number of programmes worldwide 3138. For example, Sininger et al 31 capitalised on the staggered introduction of newborn screening programmes in California to compare the average ages of screened and non-screened children with bilateral PCHI at diagnosis, fitting of amplification, and enrolment in intervention.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sininger et al 31 capitalised on the staggered introduction of newborn screening programmes in California to compare the average ages of screened and non-screened children with bilateral PCHI at diagnosis, fitting of amplification, and enrolment in intervention. They found that screened children were significantly younger at diagnosis (median age 25 months lower), at fitting of hearing aids (24 months lower), and at enrolment in early intervention (20 months lower).…”
Section: Introductionmentioning
confidence: 99%